Real-world use of fidaxomicin in a large UK tertiary hospital: how effective is it for treating recurrent disease?. Issue 2 (October 2018) - Enoch, D.A.; Santos, R.; Phillips, C.J.; Micallef, C.; Murphy, M.E.; Aliyu, S.H.; Massey, D.; Brown, N.M.
Summary: All courses of fidaxomicin use in the study hospital were reviewed. It was used for first recurrence (six times), second recurrence (eight times) and one case of third recurrence. One patients received fidaxomicin as first-line treatment. Eight patients initially responded to therapy; of these, three patients were asymptomatic at 90 days, three patients remained asymptomatic at 30 days, and two patients had recurrences five and nine days after stopping therapy. Four patients failed to respond; of these, two patients required faecal transplantation and one patient required a colectomy. Two patients deteriorated and two patients died. Fidaxomicin was well tolerated. These findings suggest that the utility of fidaxomicin at this stage of infection is unclear.